2014
DOI: 10.1039/c4cp00527a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water on the transport properties of protic and aprotic imidazolium ionic liquids – an analysis of self-diffusivity, conductivity, and proton exchange mechanism

Abstract: In this paper we report on the transport properties of protic and aprotic ionic liquids of the imidazolium cation (C2C1Im(+) or C2HIm(+)) and the TFSI(-) or TfO(-) anion as a function of added water. We observe that the self-diffusion coefficient of the ionic species increases upon addition of water, and that the cation diffuses faster than the anion in the entire water concentration range investigated. We also observe that the overall increase of anionic and cationic diffusion coefficients is significant for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
98
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(108 citation statements)
references
References 38 publications
7
98
2
Order By: Relevance
“…In that study, we hypothesized a specific interaction through the -NH group of the imidazolium ring, and observed stronger perturbations in the systems based on the TfO anion as compared to those based on TFSI. 5 Our results also suggested that the addition of water can affect the 'ionicity' of the PIL, an important aspect with respect to the use of PILs as electrolytes.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…In that study, we hypothesized a specific interaction through the -NH group of the imidazolium ring, and observed stronger perturbations in the systems based on the TfO anion as compared to those based on TFSI. 5 Our results also suggested that the addition of water can affect the 'ionicity' of the PIL, an important aspect with respect to the use of PILs as electrolytes.…”
Section: Introductionmentioning
confidence: 84%
“…6 in reference [ 5]). These findings indicate a molecular vicinity of water to the imidazolium cation as well as an NH- 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 and C 4 C 1 ImTFSI.…”
Section: Vibrational Modes Of the C 2 Him Cationmentioning
confidence: 97%
See 1 more Smart Citation
“…Ionic liquids (ILs), generally defined as organic salts that melt below 100 ∘ C, have been closely studied because they are designable, thermally stable, nonvolatile, and capable of dissolving even polymeric compounds [5][6][7]. Such properties have led to an explosion in their applications as green, designable solvents for a variety of processes linked to green chemistry and clean technology [8][9][10]. The introduction of the specific functional group in ionic liquid anions or cations is to form functional ILs [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the Proton Exchange Membrane Fuel Cell (PEMFC), which is focus of this paper, is described by the use of a polymer electrolyte membrane [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%